The Bunocephalus coracoideus Species Complex (Siluriformes, Aspredinidae). Signs of a Speciation Process through Chromosomal, Genetic and Ecological Diversity - Ferreira, Milena; Garcia, Caroline; Matoso, Daniele A.; de Jesus, Isac S.; Cioffi, Marcelo de B.; Bertollo, Luiz A. C.; Zuanon, Jansen; Feldberg, Eliana (Frontiers in Genetics, 2017)
Bunocephalus is the most speciose Aspredinidae genus, corresponding to a monophyletic clade with 13 valid species. However, many species have their classification put in question. Here, we analyzed individuals from four Amazonian populations of Bunocephalus coracoideus by cytogenetic and molecular procedures. The geographic distribution, genetic distances and karyotype data indicate that each population represents an Evolutionary Significant Unit (ESU). Cytogenetic markers showed distinct 2n and karyotype formulas, as well as different numbers and locations of the rDNA sites among ESUs. One of such populations (ESU-D) highlighted an extensive polymorphic condition, with several cytotypes probably due to chromosomal rearrangements and meiotic non-disjunctions, resulting in several aneuploid karyotypes, which was also supported by the mapping of telomeric sequences. Phylograms based on Maximum Likelihood (ML) and Neighbor Joining (NJ) analyses grouped each ESU on particular highly supported clades, the estimation of evolutionary divergence indicating values higher than 3.8% to 12.3% among them. Our study reveals a huge degree of chromosomal and genetic diversity in B. coracoideus and highly points to the existence of four ESUs in allopatric and sympatric speciation processes. In fact, the high divergences found among the ESUs allowed us to delimitate lineages with taxonomic uncertainties in this nominal species.